Tuberculosis incidence and its socioeconomic determinants: developing a parsimonious model - Sorokina, M.; Ukubayev, T.; Koichubekov, B. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Tuberculosis is a widespread communicable disease, which is one of the top 10 causes of demise globally. Several regression models have been built, and then utilized for the Tuberculosis incidence projections. However, when fitting a multiple linear regression model, an analysis must account for multicollinearity aspects. The present study aimed to develop a parsimonious model that produces unbiased results based on socioeconomic variables as predictors of Tuberculosis incidence.Study design. Ecological study.Methods. Data were collected from the Karaganda Regional Center of Phthisio-pulmonology and Bureau of National Statistics. By multiple linear regression model, we investigated associations between Tuberculosis incidence rate and socioeconomic determinants in Karaganda region, Kazakhstan, during 2001-2019. A Principal components analysis was performed on the socioeconomic variables with oblique rotation. Furthermore, associations of Tuberculosis incidence with the principal components derived from the Principal components analysis were assessed.Results. The incidence of Tuberculosis in Karaganda region decreased over the period of 2001-2019. Economic development and healthcare capacity were negatively correlated with Tuberculosis incidence. A multiple linear regression equation on Tuberculosis incidence (y) was developed with economic development (x1) and healthcare capacity (x2) clustering two components (utilizing Principal components analysis) to eliminate collinearity: y = 1442 – 454.3x1 – 211.4x2. The incidence of Tuberculosis decreased with the increase of economic development and healthcare capacity.Conclusions. In conclusion, the study indicated that economic development and healthcare capacity are closely associated with the incidence of Tuberculosis. The findings support the implementation of optimal preventive measures for Tuberculosis control, including improving the level of economic status, increasing social protection, health expenditure, and strengthening health sector capacity, which are key determinants of the incidence of Tuberculosis.